2018
DOI: 10.1074/jbc.ra118.001737
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific polyubiquitination differentially regulates parathyroid hormone receptor–initiated MAPK signaling and cell proliferation

Abstract: G protein-coupled receptor (GPCR) signaling and trafficking are essential for cellular function and regulated by phosphorylation, β-arrestin, and ubiquitination. The GPCR parathyroid hormone receptor (PTHR) exhibits time-dependent reversible ubiquitination. The exact ubiquitination sites in PTHR are unknown, but extend upstream of its intracellular tail. Here, using tandem MS, we identified Lys-388 in the third loop and Lys-484 in the C-terminal tail as primary ubiquitination sites in PTHR. We found that PTHR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 85 publications
(56 reference statements)
2
11
0
1
Order By: Relevance
“…In the absence of NHERF1, GnTI Ϫ cells express relatively little NPT2A (Fig. 6B) due to constitutive NPT2A internalization and down-regulation (11), as described previously (42). Remarkably, in both fluorescence anisotropy and coimmunoprecipitation experiments, NPT2A displayed somewhat higher binding to WT-NHERF1, essentially equivalent to the phosphomimic S290D, and much stronger than to the phosphoresistant S290A as reflected by the higher K D of 3.2 M in fluorescence anisotropy measurements ( Fig.…”
Section: Nherf1 Phosphorylationsupporting
confidence: 74%
See 1 more Smart Citation
“…In the absence of NHERF1, GnTI Ϫ cells express relatively little NPT2A (Fig. 6B) due to constitutive NPT2A internalization and down-regulation (11), as described previously (42). Remarkably, in both fluorescence anisotropy and coimmunoprecipitation experiments, NPT2A displayed somewhat higher binding to WT-NHERF1, essentially equivalent to the phosphomimic S290D, and much stronger than to the phosphoresistant S290A as reflected by the higher K D of 3.2 M in fluorescence anisotropy measurements ( Fig.…”
Section: Nherf1 Phosphorylationsupporting
confidence: 74%
“…PTHR possesses four N-glycosylation sites, and the absence of GnTI restricts PTHR glycosylation to a single Man 5 GlcNAc 2 . This residual glycosylation, however, is sufficient for PTHR function (42). PTH(1-34) elicited increases of intracellular cAMP ( Fig.…”
Section: Identification Of Nherf1 Phosphorylation Sitesmentioning
confidence: 92%
“…In this study, Leclair et al mapped the site of CXCR2 ubiquitination to a single C-tail localized lysine K 327 residue and showed that an ubiquitinationdeficient CXCR2 mutant with a K 327 to arginine (R) conversion failed to recruit b-arrestin-2 at the plasma membrane and blocked intracellular signaling including ERK1/2 phosphorylation (Leclair et al, 2014), suggesting that receptor ubiquitination is necessary for triggering signaling cascades. Agonist-induced ubiquitination of the parathyroid hormone receptor (PTHR) also requires phosphorylation and b-arrestin binding, but here ubiquitination appears to function selectively in promoting p38 MAP kinase activation and not cAMP accumulation (Zhang et al, 2018). The chemokine receptor CXCR4 has also been shown to mediate ubiquitin-dependent signaling; however, in this case the effect is indirect via modulation of signal transducing adapter molecule (STAM)-1, an ESCRT-0 component (Malik et al, 2012).…”
Section: Ubiquitin-driven Gpcr Signalingmentioning
confidence: 99%
“…4C). A more rigorous approach to identify the precise sites of GPCR ubiquitination has been determined by mass spectrometry and was shown recently for the b 2 -adrenoreceptor and PTHR (Xiao and Shenoy, 2011;Zhang et al, 2018). Ubiquitination of multiple GPCRs, including PAR1, have also been detected by curation of high-throughput proteomic mass spectrometry and low-throughput data sources and published on PhosphoSitePlus (Hornbeck et al, 2015).…”
Section: E Detection and Study Of Gpcr Ubiquitinationmentioning
confidence: 99%
“…(E) Surface biotinylation of wild-type or mutant ACE2 receptor expressed in HEK293T cells. Receptor biotinylation was performed using cleavable EZ-Link sulfo-NHS-SS-biotin as described before (Zhang et al, 2018). After unreacted biotin is quenched by ice-cold PBS containing 100 mM glycine, cells were extensively washed with PBS and lysed.…”
Section: Nherf1 Regulates Ace2-mediated Sars-cov-2 Cell Entrymentioning
confidence: 99%